2018
DOI: 10.4038/sljpsyc.v9i1.8175
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among patients at a tertiary care respiratory clinic in Sri Lanka

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Whereas the study conducted in Tertiary care of Srilanka 60.8 percent of the participants were females and the majorities (74.7%) were married. [11] Likewise, in this study 47(35.9%) of COPD patients consume alcohol and most of the COPD patients 92(70.2%) had habit of smoking, whereas, the study conducted in China which shows; nearly 40 percent of the participants had history of smoking [6] and the study conducted in rural Nepal, majority (66.9%) of the respondents in COPD group had a history of smoking and chewing tobaccos. [12] Regarding diagnosis and treatment, 86(65.2%) of the patients were diagnosed COPD within last 5 years and 92(69.7%) of the patients receiving treatment for less than 5 years.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Whereas the study conducted in Tertiary care of Srilanka 60.8 percent of the participants were females and the majorities (74.7%) were married. [11] Likewise, in this study 47(35.9%) of COPD patients consume alcohol and most of the COPD patients 92(70.2%) had habit of smoking, whereas, the study conducted in China which shows; nearly 40 percent of the participants had history of smoking [6] and the study conducted in rural Nepal, majority (66.9%) of the respondents in COPD group had a history of smoking and chewing tobaccos. [12] Regarding diagnosis and treatment, 86(65.2%) of the patients were diagnosed COPD within last 5 years and 92(69.7%) of the patients receiving treatment for less than 5 years.…”
Section: Discussionmentioning
confidence: 45%
“…[6] Likewise, study conducted in Srilanka also showed that marital status and monthly income of the participants had significant association with level of anxiety. [11] Similarly the study done in Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal revealed that patient's age, ethnicity, educational status, marital status, current working status, duration of illness, history of previous hospitalization were significantly associated with anxiety among the COPD patients. [14]…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation